2018
DOI: 10.1016/j.chembiol.2018.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Structural Determinants for Small-Molecule Activation of Skeletal Muscle AMPK α2β2γ1 by the Glucose Importagog SC4

Abstract: The AMP-activated protein kinase (AMPK) αβγ heterotrimer regulates cellular energy homeostasis with tissue-specific isoform distribution. Small-molecule activation of skeletal muscle α2β2 AMPK complexes may prove a valuable treatment strategy for type 2 diabetes and insulin resistance. Herein, we report the small-molecule SC4 is a potent, direct AMPK activator that preferentially activates α2 complexes and stimulates skeletal muscle glucose uptake. In parallel with the term secretagog, we propose "importagog" … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 46 publications
4
44
0
Order By: Relevance
“…26 ). Using a recently identified activator, SC4, it was shown that Asp111 in β2 interacts with the imidazopyridine 4ʹ-nitrogen of the compound, which could provide increased stabilization of binding to β2-containing AMPK complexes 176 . The availability of pan-β activators in addition to highly selective β1 activators has provided a useful tool for investigating β isoform-specific effects in vivo.…”
Section: ) (Table 1)mentioning
confidence: 99%
“…26 ). Using a recently identified activator, SC4, it was shown that Asp111 in β2 interacts with the imidazopyridine 4ʹ-nitrogen of the compound, which could provide increased stabilization of binding to β2-containing AMPK complexes 176 . The availability of pan-β activators in addition to highly selective β1 activators has provided a useful tool for investigating β isoform-specific effects in vivo.…”
Section: ) (Table 1)mentioning
confidence: 99%
“…The beneficial effects of these compounds remain to be fully determined. Thus, selective compounds such as MK-8722 [ 98 ] and SC4 [ 99 ] and the selective inhibitor SBI-0206965 [ 100 ] should be considered for future AMPK-targeted treatment strategies.…”
Section: Roles Of Ampk In Innate and Adaptive Immune Responsesmentioning
confidence: 99%
“…Given the high potential of the ADaM site for the design of AMPK-activating therapeutics, as well as its potential as binding pocket for hypothesized, novel physiological AMPK regulators, it is important to understand its conformational landscape and dynamics. Currently, only one crystal structure of an ADaM site ligand bound to a ␤ 2 -containing AMPK complex has been determined (26), which represents a single conformation snapshot. In contrast, biochemical characterization suggests that different ligands and different ␤ subunits induce different AMPK activity states.…”
Section: Conformational Heterogeneity Of Ampkmentioning
confidence: 99%